Management of Islamic Education Curriculum Development in Tanjungpinang City - megawati, megawati (Lembaga Penelitian dan Pendidikan Mandala, 2024)
The current phenomenon is that there are still many curricula that need improvement with regard to Islamic values. This happens due to the change of curriculum every time in the development of the learning process, one of which is in Tanjungpinang City. The purpose of this research is to further identify the administrative or management process in the development of the Islamic education curriculum in Tanjungpinang City. The research method used is to conduct a literature study process on references related to the research, this type of research is descriptive qualitative and the data analysis technique used is drawing conclusions. The results of the research obtained are (1) There is still a need for improvement of the Islamic Education curriculum at the initial level, namely public and integrated Islamic elementary schools in Tanjungpinang City, (2) The implementation of teacher capacity building in educating students by holding internal school meetings and preparing curriculum recommendations that are appropriate to be taught in public and integrated Islamic elementary schools in Tanjungpinang City. The conclusion obtained in this study is that Tanjungpinang City has endeavoured to develop Islamic education management in schools in Tanjungpinang City, especially at the elementary school level. Not only that, professional competence is carried out in the form of Continuing Professional Development (PKB) for teachers.